2006
DOI: 10.1007/s00296-006-0121-8
|View full text |Cite
|
Sign up to set email alerts
|

Raynaud’s Syndrome: comparison of late and early onset forms using hand perfusion scintigraphy

Abstract: Primary Raynaud's disease is generally a disease of younger females; however, there are cases where symptoms present over the age of 40. These cases are described as late onset. In our current prospective study we compared the characteristics of early and late onset types of primary Raynaud's in 127 patients. In addition to the collection of medical records, we performed capillary-microscopy and hand perfusion scintigraphy using Tc-99 m DTPA to evaluate the microcirculation of each patient's fingers. Regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…In agreement with previous studies [ 2 , 23 , 25 , 27 30 ], in our cohort RP was more prevalent among women than men. By contrast, the median age of patients classified as pRP (44.2 years) was older than other studies, in which the “late-onset” RP (over 40 years old) was reported in a percentage of cases ranging from 22 to 40% [ 28 , 31 , 32 ]. This could be due to the fact that the patients' recruitment was done in tertiary referral hospitals.…”
Section: Discussioncontrasting
confidence: 56%
“…In agreement with previous studies [ 2 , 23 , 25 , 27 30 ], in our cohort RP was more prevalent among women than men. By contrast, the median age of patients classified as pRP (44.2 years) was older than other studies, in which the “late-onset” RP (over 40 years old) was reported in a percentage of cases ranging from 22 to 40% [ 28 , 31 , 32 ]. This could be due to the fact that the patients' recruitment was done in tertiary referral hospitals.…”
Section: Discussioncontrasting
confidence: 56%
“…Csiki et al also reported that longer disease duration was negatively correlated with FPR. They also reported in patients with early-onset RP that the FPR was significantly lower [26].…”
Section: Results Of Perfusion Scintigraphy Of Rpmentioning
confidence: 85%
“…RP can be evaluated using perfusion scintigraphy, and there have been several studies of perfusion scintigraphy [3,[20][21][22][23][24][25]. Various radiopharmaceuticals are used, including technetium-99m (Tc-99m), diethylenetriamine pentaacetate (DTPA) [26][27][28], Tc-99m red blood cell (RBC) [20,23], Tc-99m pertechnetate [24,29], Tc-99m met hylene diphosphonate (MDP) [3], and Tc-99m hydroxymethylene diphosphonate (HDP) [22]. When the affected areas are the hands, intravenous injection of radiopharmaceuticals is done via the dorsal vein.…”
Section: Methods For Perfusion Scintigraphy For Rpmentioning
confidence: 99%
See 1 more Smart Citation